Factors influencing the use of information technology in an organization : a case study at the Centre for Modern Management (CMM) - Jap, Boon Ching (Universiti Malaysia Sarawak (UNIMAS), 2000)
This study aims to determine the level of IT use and the factors influencing the use of IT in an organization, specifically Centre for Modern Management. The factors are task characteristics, organizational context, training, availability of IT and ease of use. Moreover, the study also attempts to determine differences in the level of IT use among employees based on demographic factors (gender, age, educational and position level). The respondents consist of 37 employees at the Centre for Modern Management (CMM). A set of questionnaire is used to obtain the data. The findings show that the level of IT use in CMM is at a high usage level. There are no significant differences in IT use based on gender and age. However, there are significant differences in IT use based on educational and position level. Besides that, the study indicates that there are significant relationship between the use of IT and its factors (task characteristics, training, availability of IT and ease of use). No significant relationship between organizational context and the use of IT is found. The findings indicate that task characteristics is a dominant factor in influencing the use of IT among the employees of CMM. Suggestions are offered for further studies.